1978
DOI: 10.1073/pnas.75.1.505
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular fractionation of intra-axonally transport polypeptides in the rabbit visual system.

Abstract: We analyzed the subcellular distributions of proteins that are transported down the axons of rabbit retinal ganglion cells and compared these distributions to those of enzyme markers for endoplasmic reticulum, plasma membrane, and mitochondria. The proteins of each of five previously identified transport groups were uniquely distributed through the subcellular fractions, suggesting that each transport group is associated with different subcellular organelles. In particular, all of the observed group I polypept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
1

Year Published

1983
1983
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 28 publications
6
84
1
Order By: Relevance
“…We presume that the virus is transported across the nerve cell without replicating in the cell soma. Similar fast anterograde transport mechanisms have been widely reported for other cellular components (Couraud & DiGiamberardino, 1980;Gilbert et al, 1985;Lorenz & Willard, 1978;Lubinska & Niemierko, 1971 ;Ochs, 1972). The mean velocity of rabies virus fast transport was estimated to be in the range of 100 to 400 mm per day which is in accordance with the velocities (360 mm/day) reported for rat sensory neurons (Aquino et al, 1987).…”
Section: Retrograde and Anterograde Transport Of Rabies Virus In A Musupporting
confidence: 76%
See 1 more Smart Citation
“…We presume that the virus is transported across the nerve cell without replicating in the cell soma. Similar fast anterograde transport mechanisms have been widely reported for other cellular components (Couraud & DiGiamberardino, 1980;Gilbert et al, 1985;Lorenz & Willard, 1978;Lubinska & Niemierko, 1971 ;Ochs, 1972). The mean velocity of rabies virus fast transport was estimated to be in the range of 100 to 400 mm per day which is in accordance with the velocities (360 mm/day) reported for rat sensory neurons (Aquino et al, 1987).…”
Section: Retrograde and Anterograde Transport Of Rabies Virus In A Musupporting
confidence: 76%
“…The anterograde transport of virus is probably a complex phenomenon; perhaps it is the mode of viral entry that determines which mechanism will be used. Indeed different modes and velocities of transport have been described (Lorenz & Willard, 1978;Tytell et al, 1981). For example, different molecular forms of acetylcholinesterase are transported at various velocities ranging from 3 to 400 mm/day (Couraud & DiGiamberardino, 1980).…”
Section: Retrograde and Anterograde Transport Of Rabies Virus In A Mumentioning
confidence: 99%
“…First, radioisotopic labeling studies have provided data suggesting that many of the SCb proteins move together as if they comprised discrete structures that are transported in axons (Willard et al, 1974(Willard et al, , 1979Black and Lasek, 1980;Tytell et al, 1981;Lasek, 1981, 1982). This possibility was reinforced by studies in which large subsets of SCb proteins were isolated by subcellular fractionation (Lorenz and Willard, 1978) or nondenaturing immunoprecipitation (Black et al, 1991). Finally, a review of the literature reveals that many other SCb proteins interact with the three proteins that are cotransported in our system.…”
Section: Discussionmentioning
confidence: 96%
“…One plausible explanation for these results is that KHC-A and KHC-B were associated with different subclasses of membrane bounded organelles having different average rates. Both radiolabel studies (Lorenz and Willard, 1978) and video microscopy (Brady et al, , 1985 demonstrated that small tubulovesicular structures moved in axonal transport at a rate severalfold over that of mitochondria. If KHC-A and KHC-B represented kinesin associated with small tubulovesicular organelles and mitochondria respectively, protein markers for these structures should display transport kinetics similar to the corresponding kinesin variant.…”
Section: Comparison Of the Rate Of Movement Of Khc-a And Khc-b To Synmentioning
confidence: 99%